2015
DOI: 10.1590/0102-311x00184214
|View full text |Cite
|
Sign up to set email alerts
|

Influência do excesso de peso e da obesidade nos gastos em saúde nos domicílios brasileiros

Abstract: Influência do excesso de peso e da obesidade nos gastos em saúde nos domicílios brasileirosThe influence of excess weight and obesity on health spending in Brazilian households Influencia del exceso de peso y la obesidad en el gasto en salud en los hogares brasileños

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A study carried out with data from the Family Budget Survey, with approximately 56 thousand households, showed that overweight is directly related to the private health expenditure of Brazilian families, which can contribute to increase inequalities, since the less affluent population spends a higher proportion of their income on health when compared to the more affluent families (6% and 3.4%, respectively) [ 34 ]. In addition, being overweight brings costs to several other health care sectors.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with data from the Family Budget Survey, with approximately 56 thousand households, showed that overweight is directly related to the private health expenditure of Brazilian families, which can contribute to increase inequalities, since the less affluent population spends a higher proportion of their income on health when compared to the more affluent families (6% and 3.4%, respectively) [ 34 ]. In addition, being overweight brings costs to several other health care sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is considered a public-health problem, with both direct and indirect costs [ 1 , 2 , 3 ], such as diabetes, cardiovascular disease and hypertension, workdays lost, physician visits, disability pensions, and premature mortality [ 4 ]. In recent decades, there has been a change in eating behavior where the preference for palatable food has prevailed.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the findings of other studies, that indicate that smaller and less economically favoured regions have a higher prevalence of overweight 5,17 . In developed countries the situation is reversed, with lower classes being more affected by being overweight 1,2 . The aforementioned authors try to explain this problem by the lower prevalence of overweight in the less favoured economic classes in the developing countries, by the lack of foods for a balanced diet of nutrients, associated to a greater energy expenditure during the day, in the higher income classes the frequency of excess weight becomes…”
Section: Resultsmentioning
confidence: 99%
“…A sedentary lifestyle and a poor standard of food can contribute to excess weight gain among adolescents, considered a risk factor for diseases such as respiratory problems, diabetes mellitus, hypertension and dyslipidemia 2 , accounting for a large share of spending on public health 3 . In Brazil, data from surveys conducted by the Brazilian Institute of Statistical Geography (IBGE) showed that overweight boys aged 10 to 19 years increased from 3.7% (1974-75) to 21.7% (2008-09).…”
mentioning
confidence: 99%